The Humanities and Social Sciences in Asia: Endangered Species? - Altbach, Philip (International Higher Education, 2008)
The humanities and to a lesser extent the social sciences are in crisis in many East Asian universities. Several key challenges are evident: to improve the image of the soft sciences at every university; to provide capacity in a country to educate scholars at a high level in the various soft science disciplines (all universities of course need not offer a full range of specialties); to integrate the humanities and social sciences into interdisciplinary programs in professional and other fields; and to have capacity in these fields to contribute to general education.